Mesomóvel: uma estação meteorológica móvel de superfície para a observação de fenômenos convectivos locais - Custodio, Diogo Machado (2012)
This study presents a prototype of a deployable unit for automated surface weather observation, named Estação Mesomóvel, which is mounted on a tripod and portable in a small vehicle, allowing its installation in the path of oncoming convective storms. With a high frequency data sampling strategy, the Estação Mesomóvel is capable of monitoring adequately mesoscale surface features produced by convection. The challenges and solutions found during the conception of the prototype are discussed, as well as the results from the data comparison experiments conducted between the Estação Mesomóvel and an automated surface weather station from the operational network. The operation of the Estação Mesomóvel in storm interception mode is presented in the context of the weather analysis and forecasting strategies used, the deployment logistics, and the atmospheric data obtained in the field. Results from the analysis of the collected data showed the capability of the Estação Mesomóvel in sampling the evolution, at high frequency, of convective phenomena at the meso-g scale, such as gust fronts, cold pools, mesohighs and high precipitation rates, which are typically poorly represented by the synoptic-scale surface observing network. This investigation showed the feasibility of conducting storm interception in Brazil with the goal of collecting high-quality atmospheric data for scientific purposes.